REVIEW STUDY OF “PRAYOGIC DHUMPAN” PRACTICE AS DAILY REGIMEN - Choudhary Deepak; Rokde Varsha; Diwakar Abhinav; Jain Rekha (International Journal of Applied Ayurved Research, 2019)
Ayurved is Veda by which to know the age or attained the age It is a science which is full of secrets of the healthy life. In daily regimen, more emphasize on how to conserve our health. Acharyas clearly explain at reference of daily regimen that what we to do daily. Acharya sushuruta use a word Satatam, means maintain punctuality to follow daily regimen. This regimen by means of daily cleansing and rejuvenating of body. It is like as making your body self-contained by boost immunity. In addition, protect form emotional and seasonal outbreaks. If a person not follow pattern of Ayurvedic Dincharya they suffer from diseases of Dosha kshaya Vriddhi Vagbhata explain vata, pitta,kapha dosha increase according to day,diet,and night pattern. At the end of day, end of diet, and end of night, there is vradhi of vata dosha. At the mid of day,mid of diet and mid of night, there is vradhi of pitta dosha, At the beginning of day diet and night there is vradhi of kapha dosha . Practice of Dhumpan is described after application of Anjana for elimination of shelashma of head. Authors of Brihat-Trye (Greater Triology) acharya charak shusurut and vagbhat approaches of Dhumpana as daily practice in healthy individual and treatment of disease of upper region of body. Exact herbs, apparatus, variance application in the health and disease conditions, effects and adverse effects and contraindication are mentioned.